2013
DOI: 10.1051/parasite/2013026
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of pathogens byStomoxysflies (Diptera, Muscidae): a review

Abstract: Stomoxys flies are mechanical vectors of pathogens present in the blood and skin of their animal hosts, especially livestock, but occasionally humans. In livestock, their direct effects are disturbance, skin lesions, reduction of food intake, stress, blood loss, and a global immunosuppressive effect. They also induce the gathering of animals for mutual protection; meanwhile they favor development of pathogens in the hosts and their transmission. Their indirect effect is the mechanical transmission of pathogens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
218
0
13

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 273 publications
(235 citation statements)
references
References 101 publications
4
218
0
13
Order By: Relevance
“…On the oher hand T. evansi is well known to be mechanically transmitted by biting flies including Stomoxys and tabanid flies (Sumba et al 1998;Gutierrez et al 2010;Desquesnes et al 2013). It has been reported that trypanosomes can also develop within the midgut and hindgut of tabanid flies (Krinsky and Pechuman, 1975;Bose and Heister, 1993).…”
Section: Published Literature Has Widely Reported That Horse Flies (Tmentioning
confidence: 99%
See 2 more Smart Citations
“…On the oher hand T. evansi is well known to be mechanically transmitted by biting flies including Stomoxys and tabanid flies (Sumba et al 1998;Gutierrez et al 2010;Desquesnes et al 2013). It has been reported that trypanosomes can also develop within the midgut and hindgut of tabanid flies (Krinsky and Pechuman, 1975;Bose and Heister, 1993).…”
Section: Published Literature Has Widely Reported That Horse Flies (Tmentioning
confidence: 99%
“…Secondly, there must be a high density of potential mechanical vectors and close contact between the host animals and the vector flies (Desquesnes et al 2009). Thirdly, the biology of the flies is another contributing factor, for instance, the size of the fly mouthparts, whereby larger mouthparts of flies mechanically transmit more parasites (Sumba et al 1998;Baldacchino et al 2013). Lastly, the duration of parasite survival on the mouthparts is shorter (24 hours) as compared to inside the crop and the gut (5 to 7 days) and this would allow delayed transmission as the flies can regurgitate infected blood into the host (Baldacchino et al 2013).…”
Section: Published Literature Has Widely Reported That Horse Flies (Tmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, outbreaks of bovine anaplasmosis have been documented in some geographical areas where there are no ticks. 11 S. calcitrans, is one of the biting flies implicated in the mechanical transmission of A. marginale among bovines, 12 but there are not published reports that demonstrate this assumption. On this basis, the aim of this study was to detect DNA from A. marginale in S. calcitrans caught at 6 meters near a bovine herd, housed in pens with cement floors, which has been maintained free of ticks for 40 years, and occasionally experienced some cases of anaplasmosis.…”
Section: Introductionmentioning
confidence: 99%
“…In large herbivores, mechanical transmission by biting insects such as tabanids (Tabanidae) or stomoxes (Stomoxys spp.) is considered the primary route of infection (Baldacchino et al 2013(Baldacchino et al , 2014. However, these insects are diurnal and are attracted by large animals (Foil et al 1994) while wild rodents are small and mostly nocturnal.…”
mentioning
confidence: 99%